International intensity, diversity, and distance: Unpacking the internationalization–performance relationship. Issue 4 (August 2016) - Miller, Stewart R.; Lavie, Dovev; Delios, Andrew
Highlights: We unpack the complexity of the internationalization–performance relationship. Different mechanisms drive the performance of distinct internationalization facets. The first study to juxtapose international intensity, diversity, and distance. International intensity and distance exhibit an S-shaped performance effect. International diversity generates a U-shaped performance effect. Abstract: Prior research has considered various conceptualizations of internationalization and offered diverse perspectives on its performance implications that, in turn, have generated mixed empirical findings. We advance research on the performance implications of internationalization by uncovering the multifaceted nature of internationalization and developing a generalizable theoretical framework that unbundles internationalization into three main facets: international intensity, international diversity, and international distance. We draw from multiple disciplines to explain the causal mechanisms that underlie the distinctive performance implications of each facet and test our predictions using panel data on Japanese firms. Our findings demonstrate that international intensity and international distance produce sigmoid effects on firm performance, though for different theoretical reasons. In turn, international diversity generates a U-shaped performance effect. Our multidisciplinary perspective contributes to international business research by discerning the distinct facets of internationalization and analyzing the mechanisms that disentangle the complex nature of the internationalization–performance relationship.